Optimization of the parameters of a ground speed meter of low-flying aircraft based on the application of the theory of optimal filtration - M. E. Ivanov; V. V. Yezerskiy (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2023)
The basic principle of parametric optimization according to the criterion of minimax of variance of the resulting error of estimation of the measured parameter is considered using the example of one of the main elements of an integrated measuring system – a ground speed meter. The meter consists of a Doppler ground speed sensor (location) and an accelerometer with a longitudinal axis of sensitivity (inertial). Based on the data on their measurement errors, the coefficients of the transfer functions of each channel of the meter containing these sensors were optimized. The result of the research is a comparative analysis of the resulting accuracy of the optimized meter for the invariant and non-invariant cases, based on the obtained graphs of the frequency distribution of variances. A reasonable conclusion is made about the advantage of an invariant or non-invariant meter depending on the frequency of the signal. The Matlab R2015a software was used for calculations.